Empowered Writing : Exorcistic and Apotropaic Rituals in Medieval China. - Bumbacher, Stephan Peter (Three Pines Press, 2016)
Empowered Writing explores the inherent powers of Chinese talismans, petitions, registers, and holy scriptures, presenting a systematic study of their exorcistic and apotropaic properties. The book divides into three parts: tallies, petitions, and scriptures-all inherently empowered since they originate from the very same primordial energy as Dao, the heavens, and highest gods. Tallies emerge as certificates of legitimation, used both in the imperial government and in religion. Petitions and registers, on the other hand, are writings addressed to higher ranking spirits to control demons, disea.